Transient Stability Enhancement of DFIG based Offshore Wind Farm Connected to a Power System Network using STATCOM - Kumar, Varun; Patel, Vipin; S Pandey, A; K Sinha, S; Kumar, Dilip (International Journal of Engineering and Technology, 2018)
This paper presents the transient stability enhance of DFIG-based offshore wind farm connected power system network using STATCOM. The studied system is simulated in MATLAB/Simulink platform for study the effect of transient disturbances like, three phases to ground fault, sudden load change, voltage sag & swell. A fully aggregate model of wind DFIG is used for simulation study of system. The DFIG based wind generator, more sensitive to the grid faults than other wind generators. During transient disturbances DFIG terminal voltage reduced below the critical value and hence DFIG trips. The external reactive power support is required for stabilization of wind farm during the transient disturbances. In studied system STATCOM is used to fulfil the reactive power requirement to stabilize the wind farm. In presence of STATCOM, DFIG does not trip during transient disturbances of power system and all bus voltages & DFIG terminal voltage are also improved.Â